2022
DOI: 10.25046/aj070111
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Publicly Verifiable Proofs of Data Replication and Retrievability Applicable for Cloud Storage

Abstract: Using Proofs of Retrievability (PORs), a file owner is able to check that a cloud server correctly stores her files. Using Proofs of Retrievability and Reliability (PORRs), she can even verify at the same time that the cloud server correctly stores both her original files and their replicas. In 2020, a new PORR combined with Verifiable Delay Functions (VDFs) was presented by Gritti. VDFs are special functions whose evaluation is slow while verification is fast. Therefore, those functions help guarantee that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…However, this does not ensure that there is also the promised number of replicas available. Proof of Retrievability and Reliability (PoRR) approaches can be applied to verify this as well [117]. Here, a verifiable delay function (VDF) is applied to the data, which is slow to compute but easy to verify [118].…”
Section: Confidentialitymentioning
confidence: 99%
“…However, this does not ensure that there is also the promised number of replicas available. Proof of Retrievability and Reliability (PoRR) approaches can be applied to verify this as well [117]. Here, a verifiable delay function (VDF) is applied to the data, which is slow to compute but easy to verify [118].…”
Section: Confidentialitymentioning
confidence: 99%
“…If the response to this challenge takes too long, it is confirmed that the provider does not have the data at rest but needs to compute the VFD on the fly. In cloud-based data stores, such a procedure can also be applied efficiently [190].…”
Section: Future Prospectsmentioning
confidence: 99%